Colour–taste correspondences: Designing food experiences to meet expectations or to surprise. (1st October 2016) - Velasco, Carlos; Michel, Charles; Youssef, Jozef; Gamez, Xavier; Cheok, Adrian David; Spence, Charles
Recent research demonstrates the existence of a number of surprising associations (otherwise known as crossmodal correspondences) between seemingly non-related features in different sensory modalities, such as between basic tastes and colours. These correspondences have been incorporated into a dish called 'The Four Tastes' by chef Jozef Youssef. The dish is presented with four separate elements, each having a distinctive colour. Diners are instructed to match the colour to the appropriate taste (bitter, sweet, salty and sour). After establishing the association, the modernist chef, molecular mixologist, food designer or culinary artist can then either choose to design tasting experiences that align with these crossmodal correspondences or else play against them (to create incongruency and surprise). The former strategy typically leads to increased liking, possibly as a result of the diner being able to process the sensory information more fluently. The latter, by contrast, can elicit disconfirmed expectations, which can result in positive or negative experiences. While surprise is something that a growing number of diners are coming to expect when they visit a modernist restaurant, it tends to be a much harder approach to implement successfully in other contexts. Here, we present the literature on colour/taste correspondences, and discuss the implications of crossmodal (in)congruence in food design.